Probiotics Improve Gastrointestinal Function and Life Quality in Pregnancy - Albert T. Liu (MDPI AG, 2021)
We studied whether probiotics were beneficial for hormonal change-associated dysbiosis, which may influence the enteric nervous system and GI function during early pregnancy. The study was 16 days consisting of two cycles of six daily probiotics mainly Lactobacillus and 2 days without probiotics. Daily surveys were conducted to monitor GI function and life quality. A subset of the participants who contributed fecal specimens was used for microbiota metagenomic sequencing, metabolomics, and quantification of bacterial genes to understand potential underlying mechanisms. Statistical analyses were done by generalized linear mixed-effects models. Thirty-two obstetric patients and 535 daily observations were included. The data revealed that probiotic supplementation significantly reduced the severity of nausea, vomiting, constipation, and improved life quality. Moreover, a low copy number of fecal bsh (bile salt hydrolase), which generates free bile acids, was associated with high vomiting scores and probiotic intake increased fecal bsh. In exploratory analysis without adjusting for multiplicity, a low fecal α-tocopherol, as well as a high abundance of Akkemansia muciniphila, was associated with high vomiting scores and times, respectively. The potential implications of these biomarkers in pregnancy and GI function are discussed. Probiotics likely produce free bile acids to facilitate intestinal mobility and metabolism.